2017
DOI: 10.1093/neuonc/now231
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular characterization of multifocal glioblastoma proves its monoclonal origin and reveals novel insights into clonal evolution and heterogeneity of glioblastomas

Abstract: Background.The evolution of primary glioblastoma (GBM) is poorly understood. Multifocal GBM (ie, multiple synchronous lesions in one patient) could elucidate GBM development.Methods.We present the first comprehensive study of 12 GBM foci from 6 patients using array-CGH, spectral karyotyping, gene expression arrays, and next-generation sequencing.Results.Multifocal GBMs genetically resemble primary GBMs. Comparing foci from the same patient proved their monoclonal origin. All tumors harbored alterations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 48 publications
(68 reference statements)
10
78
0
Order By: Relevance
“…We observe a pattern of focal CNAs consistent with those described previously in [21] based only on bulk and SCS data. Previous work showed that glioblastomas tend to display at least some chromosome-scale CNAs, such as chromosome 7 gain, chromosome 9p loss and chromosome 10 loss [11,12,1]. The inferred cell components here all show gain of chromosome 7 and loss of chromosome 9p, suggesting these are early events in the tumor's evolution.…”
Section: Real Gbm Datasupporting
confidence: 49%
See 1 more Smart Citation
“…We observe a pattern of focal CNAs consistent with those described previously in [21] based only on bulk and SCS data. Previous work showed that glioblastomas tend to display at least some chromosome-scale CNAs, such as chromosome 7 gain, chromosome 9p loss and chromosome 10 loss [11,12,1]. The inferred cell components here all show gain of chromosome 7 and loss of chromosome 9p, suggesting these are early events in the tumor's evolution.…”
Section: Real Gbm Datasupporting
confidence: 49%
“…We give it a probability β 2 of tetraploidy, corresponding top ii = 1. We then allow a probability β 3 (= 1 − β 1 − β 2 ) of some other ploidy, selected uniformly from [1,3,5,6,7,8]. Currently, β 1 = 60%, β 2 = 30%, β 3 = 10%.…”
Section: A13 Semi-synthetic Data Simulationmentioning
confidence: 99%
“…Despite the common somatic 17q gain, we found significant divergence of somatic CN and mutational variants across samples, similar to what has been described in multifocal lung cancer, 21 prostate cancer, 22 and glioblastoma, 23 suggesting true multifocal primary sites of disease with independent development of tumors rather than oligometastatic spread. All somatic mutations identified were present in no more than two samples, although several have been described to have oncogenic potential and relevance in neuroblastoma, including FBN1, 24,25 FLT4/VEGFR3, 26 and N4BP1 27 (Table S1).…”
Section: Discussionsupporting
confidence: 84%
“…It is commonly assumed that tumour heterogeneity arises either from a self-renewing cancer stem cell population or due to clonal competition for common resources driven by the acquisition and expansion of mutations in cancer cells [61,[69][70][71]. Recent clinical and experimental findings have revealed extensive genetic variations in glioma cells due to intra-tumoural evolution [63,64,67,72]. Besides the large genetic heterogeneity, interactions between glioma cells and with the surrounding brain parenchyma lead to functional and phenotypic diversity.…”
Section: Intra-and Inter-tumoural Heterogeneitymentioning
confidence: 99%